PENILAIAN KINERJA KEUANGAN BANK DENGAN PENDEKATAN RISK-BASED BANK RATING METHOD - Subhan Subhan (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2019)
This study aims to assess the bank's financial performance with a Risk-Based Bank Rating approach. Risk profiles, good corporate governance, earnings, and capital are used as variables in assessing bank performance. This research uses quantitative descriptive research. The data source in this study is secondary data, while the sample used is saturated because the entire population is sampled, namely Bank Rakyat Indonesia and Bank Negara Indonesia. Based on the results of the study there is a fairly healthy predicate of the Loan to Deposit Ratio, while the ratio of Non Performing Loans, Good Corporate Governance, Return on Assets and Capital Adequacy Ratio of Bank Rakyat Indonesia and Bank Negara Indonesia are healthy categories.